Tadalafil-loaded PLGA microspheres for pulmonary administration: preparation and evaluation - Zhenlei Yang; Longmei Wang; Liu Tian; Xiuping Zhang; Guihua Huang (Universidade de São Paulo, 2019)
Tadalafil, a long-acting PED-5 inhibitor, is commonly used for the treatment of pulmonary arterial hypertension (PAH). However, its efficacy and clinical application are severely limited by the poor water solubility, low bioavailability and a series adverse effects (e.g. headaches, indigestion). In this study, tadalafil was prepared and loaded into biodegradable PLGA (poly(lactic-co-glycolic acid)) microspheres (TDF-PLGA-MS) via emulsification-solvent evaporation. The resulting microspheres were processed into pulmonary inhalant by freeze drying. The TDF-PLGA-MS was spherical and uniform, with an average particle diameter ~10.29 µm. The encapsulation efficiency and drug loading yield of TDF-PLGA-MS were 81.68% and 8.52%, respectively. The investigation of micromeritics showed that the TDF-PLGA-MS had low moisture content. The fluidity of powders was relatively good. The aerodynamic diameter and emptying rate of microspheres powders were 3.92 µm and 95.41%, respectively. Therefore, the microspheres powders were easy to be atomized, and can meet the requirements of pulmonary administration. In vitro release results showed that the microspheres group released slowly. The cumulative release in 24 h and 10 d was 46.87% and 84.06%, respectively. The in vitro release profile of TDF-PLGA-MS was in accordance with the Weibull model. The results of Pharmacokinetics showed that tadalafil from microspheres slowly released into the blood after intratracheal instillation. The pulmonary drug residue in 0.5 h was 3.5 times compared with solution group. The residual concentration in lung after 10d was still higher than that of solution group in 48 h. The t1/2β and MRT0-∞ were 3.10 times and 3.96 times that of solution group, respectively. Moreover, the Cmax and AUC of drug residues in lung were 3.48 times and 16.36 times that of solution group, respectively. The results of tissue distribution showed that the Re in lung was 16.358, which indicated the lung targeting. In conclusion, the TDF-PLGA-MS for pulmonary administration in this study can significantly improve the pulmonary targeting, increase efficacy of tadalafil and reduce other non-target organs toxicity. This study will have an important clinical significance for PAH patients who need long-term drug therapy.